1996
DOI: 10.2337/diacare.19.10.1108
|View full text |Cite
|
Sign up to set email alerts
|

Differing Effects of Pancreas-kidney Transplantation With Systemic Versus Portal Venous Drainage on Cholesteryl Ester Transfer in IDDM Subjects

Abstract: CET is affected by variations in systemic insulin levels in pancreas transplant patients with allografts that have differing venous drainage. Because high systemic insulin levels are linked to the activation of (ET, euglycemic HI IDDM pancreas allograft recipients may continue to be at high risk for macrovascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…No study demonstrated that portal venous drainage increases surgical risk 187 , 229 , 230 , 231 , 232 , 233 , 234 , 235 but, on the other hand, no study showed either an immunologic, 199 , 207 , 208 , 229 , 236 or a metabolic advantage. 233 , 234 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 …”
Section: Discussionmentioning
confidence: 99%
“…No study demonstrated that portal venous drainage increases surgical risk 187 , 229 , 230 , 231 , 232 , 233 , 234 , 235 but, on the other hand, no study showed either an immunologic, 199 , 207 , 208 , 229 , 236 or a metabolic advantage. 233 , 234 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, peripheral hyperinsulinemia has been shown to be responsible for increased LPL activity in patients with T1D (4), and it has been reported that LPL, in presence of VLDL, enhances CETP activity (35). Moreover, it has been shown that increased LPL and CETP activity in T1D patients returned to normal levels following intraperitoneal administration of insulin with an implantable insulin pump that mimics the physiologic portal route or after pancreatic graft (36,37).…”
Section: A Vldlsmentioning
confidence: 99%
“…Three articles were excluded because the data were presented in a way where it could not be extracted for meta‐analysis . Two more articles each looked at different endpoints . One study only analyzed survival estimates using Kaplan–Meier estimates , and three papers were subset analyses which included only selected recipients, and therefore, none met inclusion criteria .…”
Section: Resultsmentioning
confidence: 99%
“…Beyond glycemic control, there are proposed improvements in lipid profiles. The proposed mechanism is related to the hyperinsulinemia seen in systemic venous drainage . However, recent experimentation demonstrates that despite the fasting peripheral hyperinsulinemia, levels of intrahepatic and intramuscular lipids were similar in systemically drained pancreas transplanted individuals compared to healthy volunteers .…”
Section: Discussionmentioning
confidence: 99%